Symptomatic Avascular Necrosis: An Understudied Risk Factor for Acute Care Utilization by Patients with SCD - Yu, Tiffany (South Med J, 2016)
OBJECTIVES: Sickle cell disease (SCD) is associated with high healthcare utilization rates and poor outcomes in a subset of patients, although the underlying factors that predict this phenotype are poorly understood. Prior studies suggest that comorbid avascular necrosis (AVN) contributes to high healthcare utilization. We sought to clarify whether AVN independently predicts acute care utilization in adults with SCD and to identify characteristics of those with AVN that predict higher utilization. METHODS: We reviewed the medical records of 87 patients with SCD with symptomatic AVN and compared acute care utilization and clinical characteristics with 87 sex- and age-matched patients with SCD without symptomatic AVN. Patients with ≥2 years of follow-up were included. Outcomes were compared using bivariate analysis and multivariate regression. RESULTS: Our study included 1381 follow-up years, with a median of 7 years per patient. The AVN cohort had greater median rates of urgent care visits (3.2/year vs 1.3/year; P = 0.0155), admissions (1.3/year vs 0.4/year; P = 0.0002), and admission days (5.1 days/year vs 1.8 days/year; P = 0.0007). History of high utilization (odds ratio [OR] 4.28; P = 0.001), acute chest syndrome (OR 3.12; P = 0.005), pneumonia (OR 3.20; P = 0.023), hydroxyurea therapy (OR 2.23; P = 0.0136), and long-term transfusion (OR 2.33; P = 0.014) were associated with AVN. In a median regression model, AVN, acute chest syndrome, and pneumonia were independently associated with greater urgent care visits and admissions. CONCLUSIONS: Symptomatic AVN was found to be an independent risk factor for acute care utilization in patients with SCD. Because this is a potentially modifiable factor, further studies are urgently needed to determine whether AVN prevention/early treatment interventions will alter utilization and improve outcomes for patients with SCD.